2016
DOI: 10.4238/gmr.15038910
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and genetic changes for growth characteristics of Santa Ines sheep

Abstract: ABSTRACT. Studying genetic parameters and genetic changes in SantaInes sheep is important, because it is the commonest breed in Brazil. This study obtained genetic data from 37,735 pedigree records of lambs over 12 years (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) from 33 flocks in 10 Brazilian States; 11,851 records of performance were available. (Co)variance components, genetic parameters and breeding values estimates were obtained by derivative-free restricted maximum likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
(101 reference statements)
4
10
2
5
Order By: Relevance
“…Direct autosomal heritability estimate of 0.37 for ADG was similar to that reported by AGUIRRE et al (2016) for Santa Ines sheep (0.38). Lower direct heritability estimates were reported by ABBASI et al (2012) in Baluchi sheep, MIRAEI-ASHTIANI et al (2007) in Sangsari sheep and JAFARI and RAZZAGZADEH, (2016) in Makuie sheep.…”
Section: Discussionsupporting
confidence: 84%
“…Direct autosomal heritability estimate of 0.37 for ADG was similar to that reported by AGUIRRE et al (2016) for Santa Ines sheep (0.38). Lower direct heritability estimates were reported by ABBASI et al (2012) in Baluchi sheep, MIRAEI-ASHTIANI et al (2007) in Sangsari sheep and JAFARI and RAZZAGZADEH, (2016) in Makuie sheep.…”
Section: Discussionsupporting
confidence: 84%
“…For Santa Inês sheep, Aguirre et al (2016) found estimates of direct additive variance of 0.111 and 0.284 for the maternal permanent environment, with estimates of direct heritability and phenotypic variance explained by maternal permanent environment of 0.22 and 0.57, respectively. These authors associate these high proportions of the variance with the maternal permanent environment values, and the extensive rearing system on pasture, in which the sheep are in constant feeding transition due to the great environmental variations.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Zamani and Mohammadi (2008) and Shokrollahi and Baneh (2012) found a better fit for the model that considered the two genetic effects (direct and maternal) and the covariance between them. In turn, Aguirre, Mattos, Eler, Barreto Neto, and Ferraz (2016), observed that the best fit of the data was obtained with the model that considered, besides the direct maternal and maternal permanent environmental effects, also the covariance between the direct and maternal effects. These authors attribute the high proportions of the variance to the values of the maternal permanent environment, to the extensive farming system on pastures, in which the mothers are undergoing transitions, due to the great environmental variations.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of genetic and phenotypic parameters is important for determination of the optimal breeding strategies for the genetic improvement of the lambs' growth traits (Selvaggi et al 2011, Jafari et al 2012, Shokrollahi and Zandieh 2012, Javed et al 2013, Mohammadi et al 2013, Mokhatri et al 2013, Rashidi 2013, Jalil-Sarghale et al 2014, Al-Samarai et al 2015, Aguirre et al 2016, AL-Bial et al 2016, Bayeriyar and Hadi 2016and Jawasreh et al 2018). An accurate prediction of breeding value of growth traits of lambs is an integral part of most genetic improvement breeding programmes (Javed et al 2013, Akthar et al 2014, Roshanfekr 2014, Ahmadpanah et al 2016, Eteqadi et al 2016, Baneh and Ahmadpanah 2018, Yadavet al 2018and Sallam et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate prediction of breeding value of growth traits of lambs is an integral part of most genetic improvement breeding programmes (Javed et al 2013, Akthar et al 2014, Roshanfekr 2014, Ahmadpanah et al 2016, Eteqadi et al 2016, Baneh and Ahmadpanah 2018, Yadavet al 2018and Sallam et al 2019. Genetic trends for early growth traits of lambs of different sheep breeds have been indicated by several investigations (Mostafa et al 2011, Hossein-Zadeh 2012, Javed et al 2013, Roshanfekr 2014, Aguirre et al 2016, Ahmadpanah et al 2016, Eteqadi et al 2016, Mallick et al 2016, Baneh and Ahmadpanah 2018, Jawasreh et al 2018, Yadav et al 2018and Sallam et al 2019.…”
Section: Introductionmentioning
confidence: 99%